Perspective Of Stakeholders On The Sustainability Of Tuberkulosis Program - Indasah, Indasah; Saifulah, Dedi; Korbaffo, Anita Restu (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This research is a type of descriptive research using a qualitative approach design using a case study research design. Funding for the TB program in Pasuruan Regency was sourced from the APBD and also Health Operational Assistance sourced from the Special Allocation Fund decreased. The budget for TB prevention prevention programs is absorbed entirely But the performance of achieving the discovery targets is still not significant. Still not found the whole case, complete treatment has not been maximized, some even DO. TB control activities allocated for TB prevention and control services appear to be relatively small compared to the TB treatment budget. Based on all the challenges faced, a strategy was formulated to eliminate TB within the next 5 years by strengthening the leadership of a quality TB service program with a sustainable program across stakeholders